Elaboración de una guía sobre lingüística contrastiva para el mejoramiento del nivel de pronunciación de los estudiantes del tercer nivel de licenciatura en inglés de la universidad técnica de Cotopaxi del cantón Latacunga, provincia de Cotopaxi en el periodo 2010-2011 - Acurio Neira, Andrés Alejandro (2013)
The development of this project was focused on the necessity of improving the pronunciation skill, studying the phonetic and phonemic similarities and differences of both languages. That is why the implementation of this guide was designed in order to help the students during the learning process as a support to clear doubts about contrastive linguistics subject in a practical way. The authors used scientific and bibliographic sources to get information for the conceptual and practical frame. Additionally, this research was focused on the students’ pronunciation problems and how they understand English accents in order to improve their level of pronunciation changing the Latin accent of pronunciation into a native accent. The methods applied were deductive-inductive, which permitted extract general and specific facts about the students’ problems and the analytical-synthetic method which allows the principal problems in the ways of pronunciation. The present guide was designed to develop a new way to achieve a better level of pronunciation in order to help the students to understand and improve their speaking skill.